Modeling the dynamics of Spain's relative export strength - Sebastian Vollmer; Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmann D. (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
In this paper we assess the current relevance of Ricardian theory. Relative prices, labor costs, and productivity are evaluated as determinants of a country's international competitiveness at the industry level. Working with detailed data on unit values and with industry data on productivity, we empirically implement a MacDougall-type model for Spanish and French trade to Brazil, China, Japan, and the U.S.. The period under study is 1980 to 2001 and we distinguish in our analysis between homogenous, reference-priced, and differentiated goods. Our results indicate that Ricardian theory is currently only valid for explaining trade with developing countries while other factors are of importance for developed economies. Overall price competitiveness is of importance, but for differentiated goods, factors distinct from prices seem to determine export success.
Keywords: 330; Komparativer Kostenvorteil; Internationaler Wettbewerb; Industriegüteraußenhandel; Spanien; Frankreich; Brasilien; China; Japan; USA